PENGARUH MOTIVASI KERJA, GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN DI PT. Y - Syahrian, Syahrian; Damayanti, Tasya Eka (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Abstract: The existence of this study aims to analyze and determine the effect of work motivation, leadership style and work environment on the work discipline of the gate operational division employees at PT. Y. The form of research used is causality and descriptive research. The population used in this study were 88 employees of the gate operational division using a purposive sampling technique involving 76 employees of the gate operational division at PT. Y as the respondent. The technique used for data collection is using a questionnaire with a Likert scale. The method of analysis in this study uses multiple linear regression analysis. Based on the results of the analysis of hypothesis testing in this study that work motivation, leadership style, and work environment affect employee work discipline. Keywords: Work Motivation, Leadership Style, Work Environment, Work Discipline